BS EN 17670-1. Plastics piping systems for non-pressure underground conveyance and storage of non-potable water. Manholes, inspection chambers and road gullies for storm water systems made of unplasticized poly(vinyl chloride) (PVC-U), polypropylene (PP) and polyethylene (PE). Part 1. Specifications for storm water manholes and inspection chambers) (20th May 2021) - British Standards Institution,
No abstract available